Deciphering OPDA Signaling Components in the Momilactone-Producing Moss Calohypnum plumiforme - Inagaki, Hideo; Miyamoto, Koji; Ando, Noriko; Murakami, Kohei; Sugisawa, Koki; Morita, Shion; Yumoto, Emi; Teruya, Miyu; Uchida, Kenichi; Kato, Nobuki; Kaji, Takuya; Takaoka, Yousuke; et al. (Frontiers in Plant Science, 2021)
Jasmonic acid (JA) and its biologically active form jasmonoyl-L-isoleucine (JA-Ile) regulate defense responses to various environmental stresses and developmental processes in plants. JA and JA-Ile are synthesized from α-linolenic acids derived from membrane lipids via 12-oxo-phytodienoic acid (OPDA). In the presence of JA-Ile, the COI1 receptor physically interacts with JAZ repressors, leading to their degradation, resulting in the transcription of JA-responsive genes by MYC transcription factors. Although the biosynthesis of JA-Ile is conserved in vascular plants, it is not recognized by COI1 in bryophytes and is not biologically active. In the liverwort Marchantia polymorpha, dinor-OPDA (dn-OPDA), a homolog of OPDA with two fewer carbons, and its isomer dn-iso-OPDA accumulate after wounding and are recognized by COI1 to activate downstream signaling. The moss Calohypnum plumiforme produces the antimicrobial-specialized metabolites, momilactones. It has been reported that JA and JA-Ile are not detected in C. plumiforme and that OPDA, but not JA, can induce momilactone accumulation and the expression of these biosynthetic genes, suggesting that OPDA or its derivative is a biologically active molecule in C. plumiforme that induces chemical defense. In the present study, we investigated the biological functions of OPDA and its derivatives in C. plumiforme. Searching for the components potentially involving oxylipin signaling from transcriptomic and genomic data revealed that two COI1, three JAZ, and two MYC genes were present. Quantification analyses revealed that OPDA and its isomer iso-OPDA accumulated in larger amounts than dn-OPDA and dn-iso-OPDA after wounding. Moreover, exogenously applied OPDA, dn-OPDA, or dn-iso-OPDA induced the transcription of JAZ genes. These results imply that OPDA, dn-OPDA, and/or their isomers potentially act as biologically active molecules to induce the signaling downstream of COI1-JAZ. Furthermore, co-immunoprecipitation analysis showed the physical interaction between JAZs and MYCs, indicating the functional conservation of JAZs in C. plumiforme with other plants. These results suggest that COI1-JAZ-MYC mediated signaling is conserved and functional in C. plumiforme.